Review and Implications of Intergenerational Communication and Social Support in Chronic Disease Care and Participation in Health Research of Low-Income, Minority Older Adults in the United States - Vaccaro, Joan A.; Gaillard, Trudy R.; Marsilli, Ramces L. (Frontiers in Public Health, 2021)
Background: Health disparities disproportionally affect Black and Hispanic older US adults. Health research is needed to understand and eliminate these disparities; however, older adults, and particularly Black and Hispanic/Latino older adults are underrepresented in health research. Adult children have influenced health behavior and health outcomes of their older parents in several demographics in the US. Analysis of these studies can lead to a model for the development of interventions aimed at improving health and healthcare participation of older Black and Hispanic US adults. Objectives: To review the role of intergenerational communication and social support in health behavior, health research, and health outcomes for older adults and to apply these findings toward a model for health interventions for Black and Hispanic US older adults. Methods: An analytical narrative review and application toward an intervention model. Results: Key topic areas were reviewed and analyzed by examining studies that applied forms of intergenerational communication and/or intergenerational social support with the goal of either improving health, disease management and/or participation in health research in populations world-wide. Next, a model for providing health interventions in older Black and Hispanic US adults was developed using strategies gleaned from the findings. Conclusion: A model for health intervention for Black and Hispanic/Latino US older adults was presented based on an analytical review and intergenerational communication and/or social support. Qualitative data are necessary to understand the enablers and barriers of intergenerational communication and social support to improve health outcomes in these populations.